Nursing undergraduates experiences with nursing management subjects. - LLapa Rodriguez, Eliana Ofelia; Sirqueira Carvalho, Ticiana; Lisboa Gois, Cristiane Franca; d’Ávila Nery Guimarães, Alzira Maria (Investigación y Educación en Enfermería, 2012)
Objective. To explore the perception nursing students have towards their experiences with management subjects. Methodology. Case study, in which, content analysis and the Strengths Opportunities Weaknesses and Threats matrix were used. The research was carried out from December 2009 to August 2010. 18 nursing students from the 6th and 7th semesters of the Federal Brasileña University participated Results. From the nucleus identified the following categories emerged: 1) Nursing student and their reception in health institutions, 2) theory and practice connection, 3) professor’s role and subject organization, 4) student’s role in the subject. Possibilities and limitations about the analyzed teaching process emerged. Conclusion. The subject’s teaching-learning process is not appropriate, reason why action strategies are required to balance academic contents with local contexts.